2017
DOI: 10.1002/nur.21844
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of job resources in the relationship between job demands and interleukin‐6 in an Italian healthcare organization

Abstract: In this study we examined the association between job demands (JD), job resources (JR), and serum levels of a possible biomarker of stress, the pro-inflammatory cytokine interleukin-6 (IL-6). According to the buffer hypothesis of the Job Demands-Resources (JD-R) model, we expected that job resources-defined as job autonomy and social support from supervisor-might buffer the relationship between job demands, defined as emotional demands and interpersonal conflict with colleagues, and IL-6. Data from 119 employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 69 publications
2
17
0
Order By: Relevance
“…Accordingly, high workload may not necessarily result in WFC if teachers have adequate levels of job resources, which may help individuals to preserve or replenish personal resources such as time, energy, and mood (Bakker et al, 2011; ten Brummelhuis and Bakker, 2012). On a theoretical level, this is consistent with the buffer hypothesis of the JD-R, which claims that high job resources may offset the harmful impact of job demands on WFC (Bakker et al, 2011), job burnout (Bakker and Demerouti, 2007, 2017; Xanthopoulou et al, 2007), and work-related stress (Falco et al, 2018). Moreover, from an empirical standpoint, our findings are also consistent with the ones described by Bakker et al (2011), who found that job resources, such as PDM and supervisory coaching, attenuated the adverse effect of job demands (i.e., work overload, emotional, and cognitive demands) on WFC among medical residents.…”
Section: Discussionsupporting
confidence: 84%
“…Accordingly, high workload may not necessarily result in WFC if teachers have adequate levels of job resources, which may help individuals to preserve or replenish personal resources such as time, energy, and mood (Bakker et al, 2011; ten Brummelhuis and Bakker, 2012). On a theoretical level, this is consistent with the buffer hypothesis of the JD-R, which claims that high job resources may offset the harmful impact of job demands on WFC (Bakker et al, 2011), job burnout (Bakker and Demerouti, 2007, 2017; Xanthopoulou et al, 2007), and work-related stress (Falco et al, 2018). Moreover, from an empirical standpoint, our findings are also consistent with the ones described by Bakker et al (2011), who found that job resources, such as PDM and supervisory coaching, attenuated the adverse effect of job demands (i.e., work overload, emotional, and cognitive demands) on WFC among medical residents.…”
Section: Discussionsupporting
confidence: 84%
“…Finally, our sample of female workers is still smaller than males, and that should be expanded in the future. In addition, future research should attempt to replicate our results using not only self-report measures but also other data sources (Falco et al, 2012(Falco et al, , 2018. Moreover, future studies are needed to understand how positive supervisor behaviors may be trained to foster workplace spirituality and, consequently, its positive outcomes.…”
Section: Discussionmentioning
confidence: 83%
“…Researchers have also shown how teacher well-being could be an important determinant of student learning outcomes and students' well-being, highlighting the importance to establish the determinants not only for teachers' negative outcomes, but also positive ones that are associated to their work (Denny et al, 2011; Converso et al, 2014; Guidetti et al, 2015). Form this perspective, the present study aims to investigate teachers' well-being within the theoretical framework of the Job Demand –Resource model (JD-R model), in which job resources are all those factors that can help employees in reducing job demands and related costs (Bakker and Demerouti, 2007; Barbieri et al, 2016; Farnese et al, 2017; Falco et al, 2018; De Carlo et al, 2019). In fact, job resources include factors capable of fostering personal growth, learning and development by providing feedback, enhancing task significance, and stimulating employees' motivation (Bakker et al, 2005; Bakker and Demerouti, 2007, 2014).…”
Section: Theoretical Frameworkmentioning
confidence: 99%